Colic: Horse Owner Knowledge and Experience. (September 2015) - Bowden, A.; Brennan, M.L.; England, G.C.W.; Burford, J.H.; Freeman, S.L.
Abstract : Reasons for performing study: Colic is the most common equine emergency problem, and one of the main causes of equid deaths. The horse owners' ability to recognise colic is a critical first step in determining case outcome. Objectives: To assess equine owners' knowledge and recognition of colic. Study design: Online questionnaire of horse owners. Methods: An online survey was designed to evaluate owners' approach to colic in the horse. The survey included questions on owner demographics, their recognition of colic (including owner's opinions of their ability to recognise colic, their approach, and their recognition of colic using case vignettes), and their knowledge of normal ranges for clinical parameters. Descriptive and chi squared statistical analysis was performed. Results: The survey was completed by 1061 UK respondents. Six per cent of owners thought they could recognise all types of colic, 61% said they could recognise most cases and 30% said they could recognise some but not all cases. Owners said they would assess faecal output (73% of respondents), gastrointestinal sounds (69%), respiratory rate (62%) and heart rate (50%) in horses with suspected colic. One fifth (22%) of owners would call a vet immediately without assessing any parameters. Many respondents either did not know, or provided incorrect estimates of normal values for clinical parameters: 30.4% were 'unsure' of the normal heart rate and 35.5% gave heart rate values which were outside reference ranges; only 24.5% gave appropriate values for normal respiratory rates and only 31% gave normal temperature values. There was no statistical significance between participants' age, educational qualifications, or their experience with horses and their knowledge of normal clinical parameters. Conclusions: Owners varied in their approach and ability to recognise colic, and many had significant gaps in their knowledge of normal parameters. Educational materials and/or training to assist owners could help address these issues. Ethical animal research:  The study did not involve animal research. The study was reviewed and approved by the Ethics Committee, School of Veterinary Medicine and Science, University of Nottingham. The questionnaire was conducted in accordance with the 1998 Data Protection Act, and the British Educational Research Association's Revised Ethical Guidelines for Educational Research (2004).Source of funding:  Adelle Bowden's studentship is funded by the School of Veterinary Medicine and Science, University of Nottingham.Competing interests:  None declared.